Influência da dor neonatal e as variáveis fisiológicas mediante as condutas fisioterapêuticas em prematuros com síndrome do desconforto respiratório na unidade de terapia intensiva - Guimarães, André Gustavo Moura (2018)
Introduction: neonatal pain results in neurobiological effects, and changes in behavioral reactions of children who were born prematurely. There is no clear description about the pain caused by chest physiotherapy technique, nor about the possible non-pharmacological interventions to prevent it. Objective: to evaluate neonatal pain and physiological parameters during the chest physiotherapy in premature neonates (PTNB) in neonatal intensive care. Method: a randomized controlled trial, not blinded, in which 120 PTNB in mechanical ventilation were studied. They were randomized into four groups: control group (CG), diaphragmatic stimulation group (EDG), manual hyperinflation group (MHG), thoracic vibration group (VTG), containing 30 individuals in each one. The protocol consisted of 3 phases, the first phase being considered the control, and the other associated with non-pharmacological techniques to reduce pain: application of the technique (phase 1), application of technique + facilitated tucking (phase 2), application of technique + glucose (phase 3). Heart rate (HR), respiratory rate (RR), SpO2, Behavioral pain scale Indicators of Infant Pain (BIIP, ranges from 0 to 10) and Neonatal Infant Pain Scale (NIPS, ranges from 0 -7) were recorded at pre, during and after (15 minutes) the procedures described. Results: 62 (51.66%) RNPT were female, and most considered small for gestational age (83, 69%). Physiological variables (HR, FR, and SpO2) behaved in a similar manner in all groups (CG, MHG, EDG, VTG), being greater in phase 1, however these variables were reduced at phase 2 and 3 (p < 0.05). This means that during the application of non-pharmacological intervention (facilitated tucking or glucose) there was reduction of those variables. BIIP and NIPS scales showed increased in all of the groups in the phase 1 during the application of the techniques, however, similar to the physiological variables, these scales had reduced scores when applied to facilitated tucking (phase 2) or glucose (phase 3), p < 0.05. The number of individuals who have had pain assessed by BIIP (> 3 points) at the moment after in the phase 1 was 83 (69%), in phase 2 was 22 (18%), and in phase 3 of 34 (28%), p < 0.001. Conclusions: The chest physiotherapy techniques can increase the pain in PTNB, however, the non-pharmacological techniques, such as facilitated tucking and glucose, were able to reduce it.